Gambaran Fiksasi Jaringan Menggunakan Larutan Bouin dan NBF 10% Pada Hati Mencit Dengan Durasi Fiksasi 4 dan 16 Jam Menggunakan Pewarnaan Hematoksilin-Eosin (HE) - Ignasius Kalos; Erni Yohani Mahtuti; Faisal Faisal (Pusat Riset dan Inovasi Nasional, 2026)
Histological tissue processing remains the “gold standard” for determining patient therapy and prognosis. One of the stages of tissue processing is fixation. The types of fixative solutions used are 10% NBF and Bouin. The purpose of this study was to determine the histological features of mouse (Mus Musculus) liver tissue fixed using 10% NBF and Bouin solutions. This study used a descriptive method. The population in this study were mice. The research sample was mouse liver organs. The research stages began with mouse surgery, fixation with 10% NBF and Bouin, dehydration, clearing, embedding, blocking, cutting, and staining. The results of the histological features of mouse livers fixed using 10% NBF with a time variation of 4 hours obtained good quality preparations of 33.33% and poor quality of 66.67%. In 10% NBF with a time variation of 16 hours, good quality was obtained of 83.33% and poor quality of 16.67%. In liver tissue preparations of mice (Mus musculus) fixed using Bouin's 4-hour variation, 83.33% of good quality preparations were obtained and 16.67% of poor quality preparations. In Bouin's 16-hour variation, 33.33% of good quality preparations were obtained, 50.00% of poor quality preparations and 16.67% of poor quality preparations were obtained. Suggestions for further research on the microscopic appearance of tissue fixed using Bouin's solution and other solutions other than 10% NBF with samples other than mouse liver organs (Mus Musculus).